(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Peroxisomes are indispensable organelles in higher eukaryotes. They are essential for the oxidation of a wide variety of metabolites, which include: saturated, monounsaturated and polyunsaturated fatty acids, branched-chain fatty acids, bile acids and dicarboxylic acids [3]. However, the peroxisomal membrane forms an impermeable barrier to these metabolites. The mammalian peroxisomal membrane harbours three ATP-binding cassette (ABC) half-transporters, which act as homo- and/or heterodimers to transport these metabolites across the peroxisomal membrane.